Identification and characterization of the main forest management systems - Lima, K. Sumaya (2017)
A proficient forest management system aims to merge the sustainable use and exploitation of the forest with its conservation through a set of rules oriented towards the certification of forest management. In order to identify and characterize the main forest management systems available at the international level a scientific literature review was conducted in 24 databases. Two forest management systems internationally accepted were identified: the FSC system responsible for 39% of international forest management certifications and the PEFC system that accounts for 61%. Other forest management systems were also performed by some countries but their scope is strictly focused on the countries’ characteristics.